The Adaptability of the Indonesian Judiciary in the Era of Law and Technology Disruption - Windi Afdal; Ampuan Situmeang; Rizaldy Anggriawan; Winsherly Tan; Shelvi Rusdiana (Lex Scientia Law Review, 2025)
Legal disruption has been reported to significantly change judicial practice. Therefore, this study aims to explore 2 problem topics, namely 1) how the era of legal and technological disruption affects the profession of judges in carrying out their duties as case deciders, and 2) how is the adaptability of judges in Indonesia in facing the era of legal disruption to ensure their role and function remain relevant. The study procedures were carried out using the normative-empirical legal method, where secondary data were obtained using literature studies. Subsequently, data were enriched with empirical data obtained through field studies. The results showed Artificial Intelligence (AI) and Big Data could be integrated into the judicial system as a transformative solution due to the limited number of judges in Indonesia. The integration was expected to improve the efficiency, consistency, and unity of law enforcement. The profession of judges was required to carry out a transformation that was not only technical but also philosophical. In addition, the Supreme Court Technical Education and Training Center was expected to create an ecosystem where technology could be used as an instrument to improve the quality of Indonesian judges decisions. This could be achieved through hybrid curriculum strategies, inclusive infrastructure, and adaptive regulations.